Foreign exchange interventions in emerging market countries: New lessons from Argentina - Alexander Brause (University of Würzburg, Department of Economics, 2008)
Academic literature on foreign exchange market intervention in emerging market countries has grown in recent years. Until now, existing studies have ignored the possible feature of time varying motives and impact effects for/of interventions as well as the relationship to underlying economic and monetary policy fundamentals. Especially, for emerging markets, which are likely to face structural changes, accounting for these aspects is of crucial importance. This paper aims to contribute to this new .eld of research, by applying rolling estimation frameworks with the purpose to capture changing intervention dynamics. The used methodology allows to disentangle the evolution of intervention objectives and their effectiveness. Furthermore, the development of intervention relationships should be backed by corresponding economic and monetary policy fundamentals. Results for Argentinean experience indicate that (i) intervention motives have varied over time, (ii) impact effects were greatest when interventions were not sterilized and exchange as well as capital restrictions were in place, (iii) motive and impact eþects can be explained by economic and monetary policy fundamentals.
Keywords: C22; E52; F31; 330; Exchange rates; Intervention; Argentina; Rolling estimation; Wechselkurspolitik; Zeitökonomik; Zeitreihenanalyse; Argentinien